Prevalencia de Mycobacterium spp. en canales bovinas en el centro de faenamiento del cantón Tosagua - Orellana Castro, Emily Nicole (2024)
The study was conducted at the municipal slaughterhouse in Tosagua canton, Manabí province, with the objective of investigating the prevalence of Mycobacterium spp. in bovine carcasses. To achieve this, a combined field and laboratory protocol was applied, involving ante-mortem observation and recording of bovine physiological characteristics such as sex, age, and body condition. Subsequently, during post-mortem inspection samples were taken from affected lymph nodes, including retropharyngeal, retromammary, pre-scapular, mandibular and lung tissue, considering diameter, color, and texture. Alterations or lesions compatible with tuberculosis, such as caseous and calcified textures with yellow and cream coloring, were in 119 bovines studied, where 37 animals presented compatible lesions. Samples were cultured on Stonebrink and Ogawa Kudoh media, and bacterial growth was observed in two of them. However, using the Ziehl-Neelsen staining technique, one sample tested positive for the presence of Mycobacterium spp. determining a prevalence of 0.84% (1/119). This could be attributed to risk factors such as advanced age and low body condition, which may have facilitated the presence of the disease in the animals.